David Copperfield - Dickens, Charles
Based on the author's own life, this epic traces David's progress from his mother's sheltering arms to boarding-school and sweatshop to the rewards of friendship, romance, and self-discovery in his vocation as a writer.
Intro -- Title Page -- Copyright Page -- Introduction - CHARLES DICKENS -- PREFACE TO THE 1850 EDITION -- Table of Contents -- I. - I AM BORN -- II. - I OBSERVE -- III. - I HAVE A CHANGE -- IV. - I FALL INTO DISGRACE -- V. - I AM SENT AWAY FROM HOME -- VI. - I ENLARGE MY CIRCLE OF ACQUAINTANCE -- VII. - MY "FIRST HALF" AT SALEM HOUSE -- VIII. - MY HOLIDAYS. ESPECIALLY ONE HAPPY AFTERNOON -- IX. - I HAVE A MEMORABLE BIRTHDAY -- X. - I BECOME NEGLECTED, AND AM PROVIDED FOR -- XI. - I BEGIN LIFE ON MY OWN ACCOUNT, AND DON'T LIKE IT -- XII. - LIKING LIFE ON MY OWN ACCOUNT NO BETTER, I FORM A GREAT RESOLUTION -- XIII. - THE SEQUEL OF MY RESOLUTION -- XIV. - MY AUNT MAKES UP HER MIND ABOUT ME -- XV. - I MAKE ANOTHER BEGINNING -- XVI. - I AM A NEW BOY IN MORE SENSES THAN ONE -- XVII. - SOMEBODY TURNS UP -- XVIII. - A RETROSPECT -- XIX. - I LOOK ABOUT ME AND MAKE A DISCOVERY -- XX. - STEERFORTH'S HOME -- XXI. - LITTLE EM'LY -- XXII. - SOME OLD SCENES, AND SOME NEW PEOPLE -- XXIII. - I CORROBORATE MR. DICK, AND CHOOSE A PROFESSION -- XXIV. - MY FIRST DISSIPATION -- XXV. - GOOD AND BAD ANGELS -- XXVI. - I FALL INTO CAPTIVITY -- XXVII. - TOMMY TRADDLES -- CHAPTER XXVIII. - MR. MICAWBER'S GAUNTLET -- XXIX. - I VISIT STEERFORTH AT HIS HOME, AGAIN -- XXX. - A LOSS -- XXXI. - A GREATER LOSS -- XXXII. - THE BEGINNING OF A LONG JOURNEY -- XXXIII. - BLISSFUL -- XXXIV. - MY AUNT ASTONISHES ME -- XXXV. - DEPRESSION -- XXXVI. - ENTHUSIASM -- XXXVII. - A LITTLE COLD WATER -- XXXVIII. - A DISSOLUTION OF PARTNERSHIP -- XXXIX. - WICKFIELD AND HEEP -- XL. - THE WANDERER -- XLI. - DORA'S AUNTS -- XLII. - MISCHIEF -- XLIII. - ANOTHER RETROSPECT -- XLIV. - OUR HOUSEKEEPING -- XLV. - MR. DICK FULFILS MY AUNT'S PREDICTION -- XLVI. - INTELLIGENCE -- XLVII. - MARTHA -- XLVIII. - DOMESTIC -- XLIX. - I AM INVOLVED IN MYSTERY -- L. - MR. PEGGOTY'S DREAM COMES TRUE.
Description based on publisher supplied metadata and other sources